The Impact Of The Development Of The Tourist Object Of The Pantan Terong In Enhancing The Local Economy - Syaripuddin Syaripuddin (Proceeding International Seminar of Islamic Studies, 2019)
The study discusses the impact of developing Pantan Terong Tourism Objects in Improving the Economy of Local Communities. This type of research is descriptive with a qualitative approach. Base this research in Daling Village, Bebesen District, Central Aceh District, Aceh Province. The results of the study note that the impact of the development of the attractions of the Pantan Terong has the potential to improve the economy of the local community, this can be seen from the increasing volume of tourist visits that increase from year to year. The level of development of the attractions of the Pantan Terong has been able to improve the economy of the local community. From this research it shows that the development of the tourist object of Pantan Terong has a positive impact on improving the economy of the local community.